Gender-specific factors associated with hypertension among women of childbearing age: Findings from a nationwide survey in India - Chhabra, Pragti; Behera, Shyambhavee; Sharma, Rahul; Malhotra, Rajeev Kumar; Mehta, Kedar; Upadhyay, Kritika; Goel, Sonu (Frontiers in Cardiovascular Medicine, 2022)
Background The association of conventional (modifiable and non-modifiable) risk factors for hypertension has already been established in the literature. However, there are other putative risk factors specific to women (early menarche, age at first childbirth, women empowerment, number of children born, hysterectomy, etc.) in the development of hypertension. This study is the first study to highlight the potential association of gender-specific factors along with other conventional risk factors and hypertension, using a nationwide sample. Methods The study is a secondary analysis of the data collected from the National Family Health Survey-4 (NFHS-4), a nationally representative sample of 699,686 women of reproductive age in India. The interview schedule included data on general background characteristics, marriage, reproductive history, hysterectomy, knowledge, and utilization of family planning services, maternal and child care, women empowerment, non-communicable diseases, and domestic violence. The blood pressure was measured by direct observation by the study investigators using a digital blood pressure monitor. To account for disproportionate sampling and non-response, a weighted statistical analysis was performed. Logistic regression analysis was done to study the strength of the association between the risk factors and hypertension (computation of unadjusted and adjusted odds ratio). Results The prevalence of hypertension was 11.8% among women. Among the conventional factors, older age, higher body mass index (BMI), tobacco use, and alcohol use had higher odds for hypertension, while higher education, higher socio-economic position, and living in urban areas had lower odds. Among the gender-specific factors, younger age at first childbirth, early menarche, oral contraceptive pill use [adjusted OR: 1.23; (1.18–1.28)], and hysterectomy [adjusted OR: 1.10; (1.05–1.69)] were found to be risk factors for hypertension. Domestic violence was significantly associated with hypertension [unadjusted OR: 1.11; (1.02–1.20)]. Empowered women had lower odds of hypertension [adjusted OR: 0.93; (0.95–1.03)]. Conclusion Significant association of these gender-specific factors among women necessitates the need for taking into account these factors while screening for hypertension among women and thus, designing a tailored model better suited to them for risk assessment.